CLINICAL, NEURO-PHYSIOLOGICAL AND NEURO-VISUAL ANALYSIS OF ADULT PATIENTS WITH FOCAL EPILEPSY AND ABNORMALITIES OF CARDIAC RHYTHM AND CONDUCTION IN THE ICTAL PERIOD - Y. V. Rubleva; R. A. Teryan; G. G. Avakyan; A. A. Savenkov; Y. V. Solomatin; O. M. Oleynikova; A. M. Teplysheva; M. B. Mironov; T. M. Krasilshchikova; S. G. Burd (Эпилепсия и пароксизмальные состояния, 2018)
Objective. To conduct a survey of adult patients with focal epilepsy and ictal disturbances of cardiac rhythm and conduction, considering the disease classification, anamnesis, clinical, electroencephalographic and neuroimaging data.Materials and methods. We selected 70 patients aged 18 to 51 years old with confirmed diagnoses of focal epilepsy with epileptic seizures persisting at the time of the study on the background of antiepileptic therapy without concomitant cardiac disorders but with confirmed ictal changes in the cardiac rhythm and conduction.Results. Among the examined patients, those with long lasting “structural focal epilepsy”, frequent epileptic attacks, temporal and frontal-temporal epileptogenic foci, taking several antiepileptic drugs, prevailed. Most of the heart rhythm and conduction abnormalities occurred in male patients with serial paroxysms, bilateral tonic-clonic seizures, or sleep seizures.Сonclusion. The timely detection and examination of patients with high risk of ictal arrhythmias is able to prevent disturbances of cardiac rhythm and heart conduction during epileptic seizures, including those with a life-threatening potential.